A systematic literature review to evaluate the cardiac and cerebrovascular outcomes of patients with Fabry disease treated with agalsidase Beta - Gavin Y. Oudit; Gavin Y. Oudit; Pronabesh DasMahapatra; Nicole Lyn; Florence R. Wilson; Adekemi Adeyemi; Chae Sung Lee; Ana Crespo; Mehdi Namdar (Frontiers in Cardiovascular Medicine)
BackgroundAgalsidase beta is used to treat Fabry disease (FD); however, data on cardiac and cerebrovascular outcomes with agalsidase beta treatment come from studies with limited numbers of patients.MethodsA systematic literature review of studies reporting on the efficacy and effectiveness of agalsidase beta in FD was conducted. Studies were identified in searches of MEDLINE, Embase, and the Cochrane Central Register of Controlled Trials from January 2000–June 2022. Outcomes of interest included cardiac structure and mass, cardiac events, and cerebrovascular events.ResultsFifty-two citations (41 studies) were included. Reductions in interventricular septal thickness (IVST) and/or left ventricular posterior wall thickness (LVPWT) were demonstrated in six studies (follow-up 1–6 years, n = 4 using echocardiography, n = 2 cardiac MRI). IVST ranged from 12.1–14.9 mm at baseline and 10.8–14.1 mm at follow-up (all p < 0.05). LVPWT ranged from 11.7–16.0 mm at baseline and 10.7–13.0 mm at follow-up (all p < 0.05). Significant reductions in cardiac mass were demonstrated after 1 year of treatment in a single-arm study using cardiac MRI [left ventricular mass (LVM) 193–178 g; LVM index 102–94 g/m2; both p < 0.05]. Rates of composite cardiac events (3.8%–24.0%; four studies, follow-up 2–10 years) and cerebrovascular events (0.0%–18.9%; 12 studies, follow-up 1–10 years) were numerically lower than rates for placebo (follow-up 3 years).ConclusionLiterature over the last 20 years indicates that agalsidase beta treatment may lead to stabilization or regression of cardiac structural thickness and mass, and reduction in cardiac and cerebrovascular events relative to placebo.